2001
DOI: 10.1088/0953-2048/14/4/102
|View full text |Cite
|
Sign up to set email alerts
|

Differences in applied axial strain andIcdegradation of Bi(2223)/Ag tapes

Abstract: An experimental study of the axial strain on I c degradation of multifilamentary Bi(2223)/Ag tapes by different methods has been performed. The tapes were stressed by three kinds of tensioning set-up (expanded turn, short straight sample and U-shape spring) and the transport current versus strain I c (ε) was measured. A comparison of I c (ε) curves showed that the applied tensioning system may influence the measured sensitivity of Bi-2223 filaments, apparently against the tension strain. The lowest strain limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…A tensile load up to 1000 N applied to the specimen is transferred from sliding motion of the pusher along the bevel edge of the tension arm [18]. This allows the specimen to contract freely during cooling down to 4.2 K, which is not possible for U-shape or Walter-spiral spring systems having the sample soldered to sample holder [19,20]. The present system makes it possible to obtain σ (ε) and I c (ε) characteristics of tested sample at the same time, but it is only applicable for tension [18].…”
Section: The Tensile Test Systemmentioning
confidence: 99%
“…A tensile load up to 1000 N applied to the specimen is transferred from sliding motion of the pusher along the bevel edge of the tension arm [18]. This allows the specimen to contract freely during cooling down to 4.2 K, which is not possible for U-shape or Walter-spiral spring systems having the sample soldered to sample holder [19,20]. The present system makes it possible to obtain σ (ε) and I c (ε) characteristics of tested sample at the same time, but it is only applicable for tension [18].…”
Section: The Tensile Test Systemmentioning
confidence: 99%
“…A REVERSIBLE strain effect has been measured in many high-temperature superconductors, where the critical current I c and the flux pinning force reversibly change with the strain in Bi 2 Sr 2 CaCu 2 O x (Bi-2212) wires and tapes [1], [2], Bi 2 Sr 2 Ca 2 Cu 3 O x (Bi-2223) tapes [3]- [6], and rare earth (RE)-Ba 2 Cu 3 O 7−δ (RE = Y, Gd, Dy, Sm, etc. ; REBCO) coated conductors [7]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…The sample was soldered using a commercial Pb-63% Sn solder, and irreversible degradation occurs at tension strain of 0.57% [17]. A larger ε irr value measured here for the Ni sheathed tape can be attributed partially to an internal reinforcement by the Fe barrier and dominantly by the used U-shaped rig shunting the sample mechanically [1]. Fig.…”
Section: Methodsmentioning
confidence: 62%
“…The most used mechanical test for composite SCs is the tensile test, typically applied at room or at low (cryogenic) temperature. Several types of tensile test devices were used for characterization of composite SCs at variable strains (ε) [1]- [4]. It was shown that, in some cases, the applied measurement setup influences the critical current (I c ) characteristics of the measured sample [1], [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation